CONSCIOUS CONSUMPTION AND ITS IMPACT ON CONSUMER BEHAVIOUR: A DESK RESERACH (International Journal of Food and Nutritional Sciences, 2022)
Conscious consumption can be understood as the buying practices that encourage consumers to make purchase decisions with a positive economic, social and environmental impact. There has been growing consciousness among consumers while buying and consuming food and health-related products in the last decade due to the rise in lifestyle diseases. Also, consumers are becoming more conscious about the impact of their consumption on themselves, society and the environment. This study explores the recent trend and shifts in health-conscious consumer behaviour based on the findings and suggestions by the various researchers in their studies. Further, the study also highlights food waste management issues. The study is based on secondary data.